2008
DOI: 10.1371/journal.pone.0003081
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Empirical Evidence of Study Publication Bias and Outcome Reporting Bias

Abstract: BackgroundThe increased use of meta-analysis in systematic reviews of healthcare interventions has highlighted several types of bias that can arise during the completion of a randomised controlled trial. Study publication bias has been recognised as a potential threat to the validity of meta-analysis and can make the readily available evidence unreliable for decision making. Until recently, outcome reporting bias has received less attention.Methodology/Principal FindingsWe review and summarise the evidence fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
871
7
20

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,245 publications
(917 citation statements)
references
References 41 publications
19
871
7
20
Order By: Relevance
“…There is a widely known publication bias whereby positive results are much more likely to be published [90], which while somewhat mitigated by the inclusion of grey material, is unlikely to have been totally overcome. Additionally, as any quantitative evaluation was included, irrespective of the quality of the study design, comparing different studies to each other may misrepresent interventions’ true effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…There is a widely known publication bias whereby positive results are much more likely to be published [90], which while somewhat mitigated by the inclusion of grey material, is unlikely to have been totally overcome. Additionally, as any quantitative evaluation was included, irrespective of the quality of the study design, comparing different studies to each other may misrepresent interventions’ true effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The addition and removal of outcomes together with the sample size recalculation carry a high risk of bias. In fact, the prevalence of favourable results from the cohort of trials examined in the reported surveys is very high, and may reflect no true differences [18].…”
Section: Empirical Evidence Of Outcome Reporting Biasmentioning
confidence: 93%
“…The availability of trial protocols made it evident that often the published reports do not correspond to the registered study protocol. The findings of the principal studies that compared outcomes between protocols and publications are summarised in Table 1 (freely adapted from Table 5 of Dwan et al [18]). In comparing trial publications to protocols, Dwan's systematic review finds that 40-62% of studies have at least one primary outcome that was changed, introduced, or omitted, and that outcomes that are statistically significant have higher odds of being fully reported (range of odds ratios: 2.2-4.7).…”
Section: Empirical Evidence Of Outcome Reporting Biasmentioning
confidence: 99%
“…A related phenomenon is selective reporting of results within a study (e.g., only for certain outcome measures or subgroups among many examined), where usually those reported are statistically significant, especially in a desired or expected direction. Evidence for publication bias and selective reporting in clinical trials has been firmly established 9. For early clinical biomarker research, the potential for biases is greater due to lack of an organized system for study registration (analogous to ClinicalTrials.gov for clinical trials) and typical absence of comprehensive study protocols with prespecified statistical analysis plans.…”
Section: Introductionmentioning
confidence: 99%